Patient stratification in hepatocellular carcinoma: impact on choice of therapy. Issue 3 (4th March 2022) - Papaconstantinou, Dimitrios; Hewitt, D. Brock; Brown, Zachary J.; Schizas, Dimitrios; Tsilimigras, Diamantis I.; Pawlik, Timothy M.
ABSTRACT: Introduction: HCC comprises roughly 60 to 80% of all primary liver cancers and exhibits wide geographical variability. Appropriate treatment allocation needs to include both patient and tumor characteristics. Areas covered: Current HCC classification systems to guide therapy are either liver function-centric and evaluate physiologic liver function to guide therapy or prognostic stratification classification systems broadly based on tumor morphologic parameters, patient performance status, and liver reserve assessment. This review focuses on different classification systems for HCC, their strengths, and weaknesses, as well as the use of artificial intelligence in improving prognostication in HCC. Expert opinion: Future HCC classification systems will need to incorporate clinic-pathologic data from a multitude of sources and emerging therapies to develop patient-specific treatment plans targeting a patient's unique tumor profile.